Identifying High-Priority Populations for Dietary Salt Reduction Using the TARPARE Model: A Cross-Sectional Study - Takafumi Abe PhD; Jun Kitayuguchi PhD; Tsuyoshi Hamano PhD; Masayuki Yamasaki PhD; Shozo Yano MD, PhD; Minoru Isomura MD, PhD (SAGE Publishing, 2024)
The application of social marketing to public health activities has recently garnered attention. This study aimed to identify high-priority segments for salt reduction interventions using the TARPARE model in a rural Japanese city. This cross-sectional study used convenient sampling. Scored indicators of the TARPARE model were used, and data was collected from 1874 adults to establish the priority order of target segments for promoting salt reduction. The model considers the total number of individuals (T), at-risk persons (AR), persuasibility (P), accessibility (A), resources required (R), and equity (E). For T, the salt content was evaluated using spot urine, and the salt check sheet was scored for each segment according to sex and age in the city's population. AR was the individuals who were overweight. P was determined by the behavior modification stage of salt reduction, unknown recommended salt reduction goals, and lack of knowledge in at least one aspect of salt reduction. A and R were characterized by communication with family or friends and family support, respectively. E was considered an education up to high school. The average aggregated score was 19.9 (standard deviation = 14.0), with higher scores in segments that consistently subjectively restrict salt intake but have a high objective salt intake. The highest priority was given to women in their 60s (49.3 points) and 70s (54.4 points). This study identified high-priority populations for salt reduction in a rural city in Japan. Our priority segments offer guidance for efficient and targeted interventions for salt reduction initiatives.